Molecular characterization and novel genotypes of Enterocytozoon bieneusi in pet snakes in Beijing, China - Li, Juanfeng (Int J Parasitol Parasites Wildl, 2020)
Little is known regarding the Enterocytozoon bieneusi genotypes in snakes worldwide. In the present study, a total of 273 fecal samples were collected from pet snakes in Beijing, China. They were then tested for the presence of E. bieneusi by PCR amplification of the internal transcribed spacer (ITS) gene. The overall infection rate of E. bieneusi was 4.4% (12/273), with the highest infection rate (20%, 1/5) of E. bieneusi was found in the Black rat snake (Pantherophis obsoletus), whereas no positive samples were detected from both Milk (0/22) and Coast garter snakes (0/2). Eight genotypes were identified, including four known genotypes: EbpA (n = 1), EbpC (n = 5), Henan-III (n = 1), and SHR1 (n = 1), and four novel genotypes: CRep-5 (n = 1), CRep-6 (n = 1), CRep-7 (n = 1), and CRep-8 (n = 1). Among them, EbpC (41.7%, 5/12) was the predominant genotype. Phylogenetic analysis showed that seven genotypes belonged to group 1, while genotype SHR1 belonged to group 2. Genotypes EbpA, EbpC, and Henan-III have been previously reported in humans. This suggests that pet snakes are a potential source of zoonotic microsporidiosis transmission in China.